2022
DOI: 10.1186/s12931-022-02284-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of mast cells in the pathogenesis of severe lung damage in COVID-19 patients

Abstract: Background There is still insufficient knowledge with regard to the potential involvement of mast cells (MCs) and their mediators in the pathology of coronavirus disease-2019 (COVID-19). Therefore, our study aimed to investigate the role of MCs, their activation and protease profiles in the pathogenesis of early and late lung damage in COVID-19 patients. Methods Formalin-fixed and paraffin embedded lung specimens from 30 patients who died from COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…The limitation of this study is that the finding mainly depends on the infected mouse model and cell lines. The post-mortem lung biopsies of COVID-19 patients show a massive increase in the density of perivascular and septal MCs ( Motta Junior et al., 2020 ; Budnevsky et al., 2022 ; Schaller et al., 2022 ). Hopefully, our study would provide a clue to investigate MC role in physiological condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The limitation of this study is that the finding mainly depends on the infected mouse model and cell lines. The post-mortem lung biopsies of COVID-19 patients show a massive increase in the density of perivascular and septal MCs ( Motta Junior et al., 2020 ; Budnevsky et al., 2022 ; Schaller et al., 2022 ). Hopefully, our study would provide a clue to investigate MC role in physiological condition.…”
Section: Discussionmentioning
confidence: 99%
“…In SARS-CoV-2 infection, the post-mortem lung biopsies of COVID-19 patients show a massive increase in the density of perivascular and septal MCs ( Motta Junior et al., 2020 ; Budnevsky et al., 2022 ; Schaller et al., 2022 ). Our research, along with others’, has recently reported that SARS-CoV-2–induced massive MC accumulation and rapid degranulation caused lung inflammation and damage both in mice and nonhuman primate models ( Wu et al., 2021 , 2022 ; Tan et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Clusters of degranulating MCs expressing chymase and tryptase are seen in the lung areas with hemorrhagic phenomena, and it could be connected to local histamine production, stored endogenously within the secretory granules of MCs, and released into the vessels after cell stimulation [ 64 , 65 ]. Resident phagocyte alveolar macrophages activated by SARS-CoV-2-TLR interaction produce IL-1 which further stimulates MCs to produce IL-6 [ 65 ].…”
Section: Biological Mechanisms For In Situ Pulmonary Immunothrombosismentioning
confidence: 99%
“…Immune cells, such as macrophages, monocytes, MCs, T cells, DCs, NK cells, and neutrophils, “orchestrate” the crosstalk between proinflammatory and procoagulative networks [ 4 , 18 , 43 , 44 , 45 , 46 , 47 , 48 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 113 , 114 , 115 , 129 , 131 ].…”
Section: Figurementioning
confidence: 99%
“…In addition to being the main effector cells in type I allergic reactions, MCs are increasingly recognized for their regulatory roles in various pathophysiological processes ( Elieh Ali Komi et al., 2020 ; Lam et al., 2021 ). In SARS-CoV-2 infection, MCs are massively recruited to the alveolar septa and pulmonary parenchyma in postmortem lung biopsies of COVID-19 patients or infected monkeys ( Motta Junior et al., 2020 ; Ribeiro Dos Santos Miggiolaro et al., 2020 ; Malone et al., 2021 ; Budnevsky et al., 2022 ; Schaller et al., 2022 ). The severity of SARS-CoV-2 infection is associated with higher numbers of alveolar MCs and greater degranulation ( Krysko et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%